Legal Reformulating Illegal Parking Supervision through Participatory Governance and Sadd al-Dzari’ah Principles - Fathia Auliya Afifah; Aditya Prastian Supriyadi; Dwi Hidayatul Firdaus; Dwi Fidhayanti (Journal of Islamic Business Law, 2026)
This study is motivated by the widespread practice of illegal incidental parking during carnival events in the City of Malang, which has caused losses to the public and reflected the weak supervision of the local government. The limited resources of the Malang City Transportation Agency have hindered effective monitoring across all locations, thereby necessitating an alternative mechanism through community participation-based supervision. This research aims to examine the role of the Malang City Transportation Agency in addressing such violations and to analyze them from the perspective of sadd al-dzari’ah. This study employed an empirical juridical research method with sociological and statutory approaches. Primary data were obtained through interviews and observations, while secondary data were derived from relevant regulations and literature. The findings reveal that community participation-based supervision is implemented through public reporting, coordination with local village officials, and follow-up actions by the Transportation Agency. This mechanism is considered effective in overcoming the limitations of formal supervision and enhancing efforts to address illegal incidental parking practices. From the perspective of sadd al-dzari’ah, participatory supervision serves as a preventive measure to block pathways leading to harm, such as illegal levies, public inconvenience, and social conflict. Therefore, community involvement in supervision represents a relevant strategy that aligns with the preventive principles of Islamic law in creating order and justice in the management of incidental parking during carnival events in Malang City.